(untitled) - Foster, Vivien (Washington DC, 2005)
Water supply and sanitation in Latin America is characterized by insufficient access and in many cases by poor service quality, with detrimental impacts on public health.Water and sanitation services are provided by a vast array of mostly local service providers under an often fragmented policy and regulatory framework. Financing of water and sanitation remains a serious challenge.
Keywords: Water supply,Sanitation,Cung cấp nước,Vệ sinh; Latin America,Latin America